Malaysian consumer spending patterns during festive season - Abdullah, Nuraini; Sabriis, Mohamad Fazli (Globeedu Group, 2017)
Malaysia was recognized as a unique country where multitude of festival and events were celebrated due to multicultural community. One of the prominent festivals was EidulFitr whereby literally all Malaysian will celebrate it together. However, despite the happy celebration, some of the consumer might be with too much debt or installment as a result from excessive spending during festive seasons. Therefore, the study attempts to examine the characteristic of consumer spending pattern during EidulFitr so that precautions step can be proposed for better results. At least 748 respondents were involved in this study which distributed via online survey. Even though, previous finding ensure that consumer was over-spent especially during festive seasons but in general, the study found that most of the respondents were aware of financial planning and budgeting preparation was made to avoid over spending.